Potensi Chimeric Antigen Receptor T Cell (CAR-T Cell) dengan Target Prostate-Specific Membrane Antigen (PSMA) Termodifikasi CRISPR/Cas9 sebagai Terapi Kanker Prostat - Ali Habibi; Siti Zulaikha Risqiyani; Dwi Ari Santi Putri (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
ABSTRACT Introduction : Prostate cancer is a malignancy of prostate cells which is one of the most common malignancies in men with a prevalence of 137.9 new cases per 100,000 men each year. One of the jobs that have a high risk of prostate cancer is farmers because it is caused by exposure to pesticides and other hazardous substances. Currently, Androgen Deprivation Therapy (ADT) is still a widely used therapy. However, ADT can decrease libido, impotence, hot flashes, and an increased risk of fractures. Due to several disadvantages of ADT therapy, therapeutic innovations for prostate cancer are needed. Method : PRISMA which is based on facts and random data collection by entering predetermined keywords. Of the 94 journals that have been reviewed, 64 of them are considered according to the topic of discussion and are used as references. Results and Discussion : CAR-T Cell modified CRISPR / Cas9 injected into mice proved to be efficient and effective in increasing the function of CAR-T Cell. The immunosuppressive mechanism caused by PD-1 binding with PD-L1 can be resolved using the CRISPR / Cas9-mediated anti PD-1 method so that it can maintain CAR-T Cell activation. Evidenced by the increase in CAR-T cell degranulation and tumor clearance in the in vivo test. Conclusion : Chimeric Antigen Receptor T Cell (CAR-T Cell) with a CRISPR/Cas9 modified Prostate-Specific Membrane Antigen (PSMA) target has the potential to be an effective therapeutic innovation for prostate cancer.